Borys Pasternak wobec ideologii swoich czasów - Zygmunt Zbyrowski (Studia Rossica Posnaniensia)
Boris Pasternak avoided open ideological declarations. We usually discern his attitude and views from his works. As an active participant of the intellectual and artistic life of his times, however, Pasternak was compelled to opt for a standpoint regarding the problems faced by Russian society at the time. The poet represented a certain attitude towards such ideological issues as revolution, anti-Semitism, feminism, the role of Christianity in history, and new ideas and trends in art. Other ideologies such as ecology, Tolstoyism and Marxism, to which he attached lesser importance, should also be mentioned.